IMPLEMENTASI PELAKSANAAN E-KATALOG LOKAL DI KABUPATEN OGAN KOMERING ULU DALAM RANGKA MENINGKATKAN KEIKUTSERTAAN PELAKU USAHA MIKRO, KECIL, DAN MENENGAH: Pendahuluan, Metode, Pembahasan, dan Daftar Pustaka - Aldi Setiawan Setiawan; Achmad Zahruddin; Rakhmat Saleh; Santi Indriani (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2025)
ABSTRACT Local E-Catalog is an application created by the Government Goods and Services Procurement Policy Institute which functions to display provider products, especially MSME products. However, the small number of MSMEs joining the local e-catalog is a problem that must be addressed by the Ogan Komering Ulu Regency Government. The background to the problem is how to implement local e-catalogs in Ogan Komering Ulu Regency in order to increase the participation of micro, small and medium enterprises. The aim of this research is to increase the participation of micro, small and medium enterprises to join local e-catalogues. This research was conducted on October 6 2023 at the Regional Secretariat Office of Ogan Komering Ulu Regency in the Goods and Services Procurement Unit Section. This research uses qualitative research with a case study approach. The data sources used are primary data and secondary data. This research produces a conclusion that the implementation of the local e-catalog in Ogan Komering Ulu Regency is going quite well and there is an increase in MSME actors joining the local e-catalog, although it is not yet optimal. This is assessed from four indicators of policy implementation according to Edwards, namely communication, resources, disposition or tendencies of implementers, and bureaucratic structure. From the four assessment indicators, it can be said that the implementation of the local e-catalog in order to increase the role of MSME actors in joining the local e-catalog is going quite well, although there is a tendency for implementers, namely that some MSME actors are not interested in joining the local e-catalog. The researcher's suggestion is that gradual outreach and technical outreach to non-providers is a solution to increase the participation of MSMEs in joining local e-catalogs. Keywords: Policy Implementation, Local E-catalog, and Micro, Small and Medium Enterprises (MSMEs)